A Hellenistic invention: the construction of the idea of Judaism in opposition to Hellenism in the book of ‘2 Maccabees’ - Ruppenthal Neto, Willibaldo (Romanitas - Revista de Estudos Grecolatinos, 2019)
This article aims to analyze the construction of the Jewish identity in the book of 2 Maccabees from the use of the Greek term Ἰουδαϊσμός in opposition to the term Ἑλληνισμός which is re-signified as the Greek way of life. It is intended to analyze how the construction of the idea of ​​“Judaism” from the opposition to the idea of ​​“Hellenism” resembles the previous construction of the idea of ​​“barbarian” and the later idea of ​​“Christianity”, emphasizing the importance of the opposition as a mechanism of cultural identities in Antiquity.
Keywords: Judaism; Hellenism; Hellenistic period; Identity; 2 Maccabees